Analysis of Students Errors in Application Integrals Materials - Solfitri, Titi; Maimunah, Maimunah (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research aimed to analyze the studentsâmistakes based on Newman error analysis. Newman Error type consists of reading error, understanding the mattererror, the transformation error, processing skillserror, and writing down the answers errors. Qualitative research uses to descriptive describe the symptoms or the circumstances of the students in solving the matter on integral application. The research was conducted in the S-1 Study Program of Mathematics Education in 2017/2018 with the subject as many as 6 students who have low, medium and high competency respectively 2 students. The researcher gave two questions about the application integral to the students and then the results were analyzed and interviews were conducted to obtain information on students errors in solving problems.The analysis result shows that studentswith low competency experienced in reading error, comprehension error, transformation error, process skills error, and encoding error. This is because the students do not really understand the integral application materials. The students with medium competency in an underwenterror in process skills and writing the final answers. While the high-competence students had an error in writing the final answer. Overall, most students experienced errors at the stage of understanding the problem. This happens because the students do not read and understand the questions carefully so the students are not able to understand the matter. In the end the students make mistakes of writing down the answers